Security software development for arduino-robot motion control - Olaide Jamiu Olalekan (ХНУРЕ, 2019)
The given work is devoted to the software development for Arduino-Robot motion control. There is considered the mobile robotics application, the general approach to a mechanical design, security software mechanisms for developing, the description of Arduino-Robot platform and the methods of motion control is explained. The main steps for development Arduino-Robot is described in this paper. During execution, these steps it is developed the software for Arduino-Robot control with application of different motion algorithms and programming procedure